Kinetics Modelling of Uncatalyzed Esterification of Acetic Anhydride with Isoamyl Alcohol in a Microreactor System. Issue 3 (June 2021) - Lee, C.S.; Vorwerk, C.; Azudin, N. Yusoff; Ahmad, N.A.; Shukor, S.R. Abd
Abstract: Uncatalyzed esterification of acetic anhydride and isoamyl alcohol has been carried out in a miniaturized intensified reactor (MIR) to develop a kinetic equation using an ideal homogenous model. The effect of reaction temperature (65 ℃ -85 ℃ ) and residence time (7.9–180.3 min) at constant molar ratio 2:1 of isoamyl alcohol to acetic anhydride were studied. The results showed that isoamyl acetate concentration production increased from 0.80 mol/L to 2.64 mol/L with residence time from 7.9 min to 180.3 min and also increased from 1.6 mol/L to 2.0 mol/L when reaction temperature increase from 65 ℃ to 85 ℃ . High conversion (>97%) of acetic anhydride was obtained in the absence of a catalyst in a microreactor system in a short residence time of 90 min as compared to days in a traditional batch reactor. This is because of the high surface-to-volume ratio of a microreactor system which promotes excellent proximate contact between reactants to allow efficient heat and mass transfer for esterification and effective mixing. Three different kinetic equations which are the second-order model, autocatalytic and reversible reaction were used to fit the experimental data. The latter kinetic model represented well for the esterification reaction between acetic anhydride and isoamyl alcohol with a good fit of 0.38 average standard error of regression between predicted concentration compare to experimental result. From the simulation result, hydrolysis of isoamyl acetate was found to be more favorable compared to acetic anhydride. This can be seen from the rate constant of reverse reaction of isoamyl acetate, where k 3 = 0.008530 L mol . s which is significantly higher compare to hydrolysis of acetic anhydride, where k 4 = 3.983 × 10 − 8 L mol . s at initial water concentration of 0.2 M. Even at different simulated initial water concentration, rate constant of hydrolysis of isoamyl acetate, k 3 was always greater than the hydrolysis of acetic anhydride, k 4 . The parameter of initial water concentration was important to be determined in which it allows to improve the fitness of the kinetic model. Graphical abstract: ga1 Highlights: Reversible model chosen as the suitable model to describe uncatalyzed esterification in microreactor system Benefit of microreactor system enhance reaction rate of esterification compare to batch reactor. High conversion (>97%) able to obtained which comparable to catalysed esterification in batch system at low residence time Reversible kinetic model well fitted the experimental data with average standard error of regression of 0.38 Presence of initial water concentration result in complex reaction which lead to hydrolysis of acetic anhydride and ester.